2DEG and 2DHG in NaTaO3 polar thin films: thickness and strain dependency. (4th February 2021) - Portugal, Guilherme Ribeiro; Teodoro Arantes, Jeverson
Abstract: Two-dimensional (2D) carrier gases in perovskite surfaces and interfaces have been intensely studied since their properties are attractive to many functional devices and applications. Here, we demonstrate through ab initio DFT calculations that surface 2D carries gases can be found in NaTaO3 ultrathin films. Furthermore, we show the thickness dependence of such phenomenon and how it can be tuned when biaxial in-plane strain is applied. Tensile does not alter the valence and conduction character of the films but promotes 2D electron and hole gases in the (TaO2 ) + and (NaO) − surfaces, respectively. Because of the competition between surface and strain effects to deal with the cleavage-induced polarity, biaxial compression is able to generate 2D hole gases in the (TaO2 ) + surface instead. Such carrier-type and layer switching are explained through changes in the electrostatic potential balancing along the [001] direction and (Na, Ta) cations displacements. The presented results concern not only nanoelectronics but also catalytic applications where modulating bandgap and valence/conduction states is desired.